1997
DOI: 10.1121/1.420585
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and visual studies of blue whales near the California Channel Islands

Abstract: Preliminary results are presented from a combined acoustic and visual study of blue whales in the Channel Islands National Marine Sanctuary off the California coast, conducted during four 3-day expeditions in July 1996. Acoustic recordings were collected using GPS positioned sonobouys arrays, with up to five sonobuoys deployed at approximately 1-km spacing. Visual observations were made to estimate the number of blue whales in the vicinity of the arrays, and to record whale behaviors. Significant numbers of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Arch call detection in the St. Lawrence was limited ͑n =6͒ and was not associated with AB phrases as in the other Atlantic studies ͑Mellinger and Nieukirk et al, 2004͒. Overall, the audible downsweep calls from this study fall within the same frequency band and time span as those previously reported worldwide ͑Thompson et al, 1996;Aburto et al, 1997;Ljungblad et al, 1997;Teranishi et al, 1997;Ljungblad et al, 1998;Thode et al, 2000;Watkins et al, 2000;McDonald et al, 2001;Mellinger and Clark, 2003;Oleson et al, 2003; McDonald, in press͒. Although it is thought that audible downsweep calls do not show geographic variation, a more comprehensive and detailed comparison between regions may provide evidence to the contrary.…”
Section: B Audible Callssupporting
confidence: 70%
See 1 more Smart Citation
“…Arch call detection in the St. Lawrence was limited ͑n =6͒ and was not associated with AB phrases as in the other Atlantic studies ͑Mellinger and Nieukirk et al, 2004͒. Overall, the audible downsweep calls from this study fall within the same frequency band and time span as those previously reported worldwide ͑Thompson et al, 1996;Aburto et al, 1997;Ljungblad et al, 1997;Teranishi et al, 1997;Ljungblad et al, 1998;Thode et al, 2000;Watkins et al, 2000;McDonald et al, 2001;Mellinger and Clark, 2003;Oleson et al, 2003; McDonald, in press͒. Although it is thought that audible downsweep calls do not show geographic variation, a more comprehensive and detailed comparison between regions may provide evidence to the contrary.…”
Section: B Audible Callssupporting
confidence: 70%
“…This call type also occurs worldwide but does not show the obvious geographic variation seen with the low-frequency vocalizations. Although these higher-frequency calls occur worldwide, they are mostly reported by studies conducted in coastal waters ͑Thompson et al, 1996;Ljungblad et al 1997;Teranishi et al, 1997;Thode et al, 2000;McDonald et al, 2001;Bass and Clark, 2002͒. It should be noted, however, that with the exception of Stafford et al ͑2001͒, many deep basin datasets have not yet been fully analyzed for this call type ͑Clark, 2003; Moore, 2005͒. For simplicity, the low-frequency and higher-frequency blue whale call types will be referred to as infrasonic and audible calls, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the original time series produced by the whale can be estimated, using multichannel deconvolution methods. 15,16,61 During its final dive before passing FLIP, this whale generated three strong ''type D'' FM downsweeps, 10 plotted in Fig. 9͑a͒.…”
Section: Source Signature Recovery For Casementioning
confidence: 99%
“…The ''type A'' and ''type B'' eastern Pacific blue whale vocalizations discussed here are described in greater detail elsewhere. [8][9][10]17,18 References on blue whale sounds in other regions of the world, [19][20][21][22][23][24][25] MFP, 1,2,26,27 and geoacoustic inversion methods, 26,[28][29][30][31][32][33][34] have also been provided.…”
Section: Introduction and Review Of Previous Workmentioning
confidence: 99%
“…A few blue whales are seen in the Sea Range and nearby areas in early-to-mid spring (four sightings), but they are most common during the July to September period (43 sightings in July and 65 sightings in August and September during the surveys summarized in Figure 3.7-49; see also Teranishi et al 1997). In some years blue whales are common in and adjacent to the Sea Range as late as mid-October (e.g., in 1995, Spikes and Clark 1996;Clark and Fristrup 1998;Clark et al 1998).…”
Section: Blue Whale Balaenoptera Musculusmentioning
confidence: 99%